Analisis Faktor-Faktor yang Mempengaruhi Tingkat Kepuasan Konsumen dalam Mengonsumsi Kopi Bubuk Amabidiru di Kabupaten Kepulauan Yapen - Agoeng Karyanto; Rosalyn Gracya; Hana Kapanai (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This researc aims to find out whether the price,brand image and product quality influence the level of consumer satisfaction. This type of research was chousen because the aim of this research is to identify factors that influence the level of consumer satisfaction in consuming Ambaidiru coffe in the regency Yapen Islands.The population in this study was a total of 80 consumers and 40 people were taken as sample. The data in this research was obtained through a questionnaire method given to respondents selected as research samples. The questionnaire is prepared based on research variables that had been identified. Based on the results of the F test,namely 20.660. Meanwhile,the significance value is 0.00, which is smaller than 0.05. It can be concluded that product qualiti price and brand image have a simultaneous influance on consumer satifaction.